Impact of a Carbapenem Antimicrobial Stewardship Program on Patient Outcomes - Seah, Valerie Xue Fen (2018)
Antimicrobial stewardship programs (ASPs) aim to improve appropriate antimicrobial use. However, concerns of the negative consequences from accepting ASP interventions exist, particularly when deescalation or discontinuation of broad-spectrum antibiotics is recommended. Hence, we sought to evaluate the impact on clinical outcomes when ASP interventions for inappropriate carbapenem use were accepted or rejected by primary providers. We retrospectively reviewed all carbapenem prescriptions deemed inappropriate according to institutional guidelines with ASP interventions between July 2011 and December 2014. Intervention acceptance and outcomes, including carbapenem utilization, length of stay, hospitalization charges, 30-day readmission, and mortality rates were reviewed. Data were analyzed in two groups, one in which physicians accepted all interventions (“accepted”) and one in which interventions were rejected (“rejected”). A total of 158 ASP interventions were made. These included carbapenem discontinuation (35%), change to narrower-spectrum antibiotic (32%), dose optimization (17%), further investigations (including imaging and procalcitonin) (11%), infectious diseases referral (3%), antibiotic discontinuation (other than carbapenem) (1%), and source control (1%). Of 220 unique patients, carbapenem use was inappropriate in 101 (45.9%) patients. A significant reduction in carbapenem utilization was observed in the accepted group versus rejected group (median defined daily doses, 0.224 versus 0.668 per 1,000 patient-days, respectively; P < 0.001). There was a significant reduction in 30-day mortality in the accepted (none) versus rejected group (10 deaths, P = 0.015), but there were no differences in length of stay, hospitalization charge, or 30-day readmission rates. Hypotension was independently associated with mortality in multivariate analysis (odds ratio, 5.25; 95% confidence interval, 1.34 to 20.6). In our institution, acceptance of carbapenem ASP interventions did not compromise patient safety in terms of clinical outcomes while reducing consumption.